Platelet function profiles in the elderly: Results of a pharmacodynamic study in patients on clopidogrel therapy and effects of switching to prasugrel 5 mg in patients with high platelet reactivity - Capranzano, Piera; Tamburino, Claudia; Capodanno, Davide; Miccichè, Eligio; D’Urso, Lucia; Calvi, Valeria; Angiolillo, Dominick J.; Tamburino, Corrado (Thrombosis and Haemostasis, 2011)
Studies specifically designed to assess clopidogrel response in the elderly as well as treatment alternatives to improve platelet inhibition in this highrisk population are lacking. This study aimed to define phar-macodynamic (PD) profiles, including high platelet reactivity (HPR) rates, among elderly patients on maintenance clopidogrel therapy and to assess the PD effects of prasugrel 5 mg/day in elderly with HPR. This was a prospective observational PD study enrolling consecutive ≥75-year-old patients on maintenance clopidogrel therapy (75 mg/day) who were tested for clopidogrel response by the VerifyNow P2Y12 assay and light transmittance aggregometry (LTA). HPR rates were estimated using multiple definitions. HPR patients identified by the VerifyNow P2Y12 assay [P2Y12 reaction unit (PRU) ≥230] were switched to prasugrel 5 mg/day, and platelet function testing was performed after 15 days of treatment. PD testing was completed in 100 patients. The HPR prevalence varied between 25% and 32%, depending on the definition used. A PRU ≥230 was observed in 25 patients; of these, 20 switched to prasugrel 5 mg/day. This resulted in significant reduction in PRU mean values (279.8 ± 45.1 vs. 171.7 ± 65.2, p=0.0002) with an absolute between-treatment difference of 108.1 (95% confidence intervals 75.2–140.9). Accordingly, switching to prasugrel 5 mg/day overcame HPR in most (80%) patients. Consistently, all LTA measures were significantly lower after prasugrel compared with clopidogrel. In conclusion, a considerable proportion of elderly patients exhibit HPR while on standard clopidogrel therapy. Switching to 5 mg/day prasugrel in elderly patients with HPR is associated with enhanced platelet inhibition and overcomes HPR in the majority of these patients.
Keywords: Clopidogrel non-responsiveness; elderly patients; prasugrel